ANALISIS PENGAKUAN PENDAPATAN PADA PERUSAHAAN KONSTRUKSI - Elmira Febri Damayanti (Universitas Muhammadiyah Metro, 2016)
Most companies aim to maximize profit or gain. Therefore, one element of which is related to the size of the profit generating companies is revenue. In the construction company, there are two methods of revenue recognition are completed contract method and the percentage of completion method. The purpose of this research is to find out which kind of method that is suitable for Nolimax Jaya Ltd. Co. The analytical method used is descriptive method that describes a situation objectively. Data collected by observation, interviews, and used documentation and literature are relevant to this research.The survey revealed that the company used the percentage of completion method with physical progress approach. Based on the result, the company recognized a higher income or overstatement when compared with the cost to cost approach. The cost to cost approach provide a more reasonable because it recognizes revenue based on costs incurred that reflect the completion stage in the current period and in accordance with the matching principle and the principle of conservatism in financial statement presentation. Keyword: Revenue recognition, physical progress approach, and cost to cost approach